Sisyphus in Castle Improving European Union Strategies for Democracy Promotion and Governance Conditionality - Santiso, Carlos
At firts sight, the IMF's good governance agenda appears to be a politically progessive addition to fund policy. However, drawing on the experience of the Asian financial crisis, this article argues that governance is too politically complex an significant to fit comfortably with the fund's existing mandate